Saving for Development: A Linkage Model for Informal and Formal Financial Markets - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1985)
The policy of development through subsidized credit has largely failed. Development policy is presently being reoriented towards savings mobilization supplement by credit programs based on personal savings. Formal financial markets are ineffective in mobilizing savings in Third World countries as they reach but a small proportion of the population. Most of the rural and urban masses have only access to informal financial markets. The most prominent financial self-help organizations are savings and credit associations, which particularly widespread in West Africa: formal organizations on an informal market.The effectiveness of both formal and informal financial markets is greatly enhanced by linking savings and credit associations to formal financial institutions. The associations are formed into joint and several liability credit groups obtaining group credit for lending to members. After an initial phase of quanitiative growth, they offer consultancy and other services to their members, possibly with the assistance of an aid project, thus contributing to a qualitative development process. – – Nach dem Scheitern einer finanzwirtschaftlichen Politik subventionierter Kredite findet zur Zeit eine entwicklungspolitische Umorientierung auf Ersparnismobilisierung und ersparnisabhängige Kreditvergabe statt. Formelle Finanzmärkte eignen sich nur in beschränktem Maße für eine Ersparnismobilisierung in Entwicklungsländern, da sie nur einen geringen Teil der Bevölkerung erreichen; den ländlichen und städtischen Massen sind weitgehend nur informelle Finanzmärkte zugänglich. Die wichtigste finanzielle Selbsthilfeorganisation ist der Spar- und Kreditverein (SKV), der besonders weit in Westafrika verbreitet ist: eine formelle Organisation auf einem informellen Markt. Die Wirksamkeit formeller und informeller Finanzmarkte lässt sich erheblich steigern, indem SKV an formelle Finanzinstitutionen angebunden werden. Da Vereine wandeln sich in Kreditgruppen mit gesamtschuldnerischer Haftung um und erhalten einen Gruppenkredit, den sie an die Mitglieder durchleiten. Nach einer ersten Phase quantitativen Wachstums tragen sie durch Beratungsdienste und andere Leistungen für ihre Mitglieder zu einem qualitativen Entwicklungsprozess bei, gegebenenfalls mit Unterstützung eines Entwicklungsprojektes.
Keywords: 330; Finanzmarkt; Entwicklungsländer